Técnicas de lectura y su incidencia en el aprendizaje de los estudiantes del septimo año paralelo A de Educación General Básica de la Escuela Carlota Jaramillo, período 2016-2017 - Molina Hidalgo, Mayra Elizabeth (2017)
The reading difficulties that the students presented had an impact on learning a problem detected once the survey, interview and through daily observation were applied to most of the children, affecting their academic and social life, for this reason this topic was raised to carry out the project in the School of Basic Education "Carlota Jaramillo" being the average reading of acquiring new knowledge with it we enrich our vocabulary, it is an interactive process of communication, which establishes a relationship between the text and the reader. The purpose of the research was to create a reading habit, better reading comprehension almost in most students, helping to retain knowledge acquired by increasing reasoning ability motivating them to read comics, stories, novels, magazines and other texts to wake up curiosity to learn, discover new things and apply it in daily life obtaining as a result to raise the academic performance in the students. The methodology used for the execution of the research was the scientific, bibliographic and statistical method, which was of great help for the collection of information. The contribution that the project provides is to improve students' learning by forming analytical human beings, critics capable of expressing their ideas, feelings and emotions without fear, motivated students to read, reflect, understand and make sense of the text they read. . By means of the socialization of a seminar workshop, the benefits of reading techniques were explained in a clear and precise way to have a good communication between human beings that is important in the integral formation of the students. It is a human capacity that allowed the learning of various subjects, so the act of reading should not be seen as a mechanical activity but as the path of knowledge.